Engaging citizens in sustainability research: comparing survey recruitment and responses between Facebook, Twitter and qualtrics. Issue 9 (6th April 2021) - Bridge, Gemma; Armstrong, Beth; Reynolds, Christian; Wang, Changqiong; Schmidt, Ximena; Kause, Astrid; Ffoulkes, Charles; Krawczyk, Coleman; Miller, Grant; Serjeant, Stephen; Oakden, Libby
Abstract : Purpose: The study aims to compare survey recruitment rates between Facebook, Twitter and Qualtrics and to assess the impact of recruitment method on estimates of energy content, food safety, carbon footprint and animal welfare across 29 foods. Design/methodology/approach: Two versions of an online survey were developed on the citizen science platform, Zooniverse. The surveys explored citizen estimations of energy density (kcal) or carbon footprint (Co2 ) and food safety or animal welfare of 29 commonly eaten foods. Survey recruitment was conducted via paid promotions on Twitter and Facebook and via paid respondent invites on Qualtrics. The study included approximately 500 participants (Facebook, N ˜11 (ratings 358), Twitter, N ˜85 (ratings 2, 184), Qualtrics, N = 398 (ratings 11, 910)). Kruskal–Wallis and Chi-square analyses compared citizen estimations with validated values and assessed the impact of the variables on estimations. Findings: Citizens were unable to accurately estimate carbon footprint and energy content, with most citizens overestimating values. Citizen estimates were most accurate for meat products. Qualtrics was the most successful recruitment method for the online survey. Citizen estimates between platforms were significantly different, suggesting that Facebook and Twitter may not be suitable recruitment methods for citizen online surveys. Practical implications: Qualtrics was the favourable platform for survey recruitment. However, estimates across all recruitment platforms were poor. As paid recruitment methods such as Qualtrics are costly, the authors recommend continued examination of the social media environment to develop appropriate, affordable and timely online recruitment strategies for citizen science. Originality/value: The findings indicate that citizens are unable to accurately estimate the carbon footprint and energy content of foods suggesting a focus on consumer education is needed to enable consumers to move towards more sustainable and healthy diets. Essential if we are to meet the 2030 Sustainable Development Goals of zero hunger, good health and wellbeing and responsible consumption and production. The study highlights the utility of Zooniverse for assessing citizen estimates of carbon footprint, energy content, animal welfare and safety of foods.